Video analysis of wing clicking in Cicadas of the genera Cicadatra and Pagiphora (Homoptera: Auchenorrhyncha: Cicadoidea) - Gogala, Matija (Acta entomologica slovenica (Ljubljana), 2003)
Wing clicking or clapping sound producing mechanism has been investigated in cicadas Cicadatra atra, C. persica and Pagiphora annulata, using a low cost HS (high speed) video camera. The main conclusion is that clicks are not produced by banging tegmina against each other, the body or substrate. Sounds occur when the front wings or tegmina are in the half open position. This fact, the occurence of preclicks some milliseconds before the main click and some other data suggest the existence of a bistable clicking mechanism in the front wings.
Keywords: bioakustika; entomologija; oglašanje; škržati